PERFORMANCE-BASED BUDGET DETERMINATION AT THE AIRPORT AUTHORITY OFFICE OF REGION VI PADANG - Risa Wahyuni EDT; Fathiah Fathiah (Jurnal Akuntansi Syariah (JAkSya), 2025)
This study aims to determine the effect of internal control and organizational commitment on performance-based budgeting at the Airport Office of Region VI-Padang. The problem in this study is weak internal control, especially in the supervision of official vehicles and the lack of organizational commitment to follow up on findings related to violations of Standard Operating Procedures (SOP). The type of research used in this study is field research with a quantitative approach. The sample used a total sampling of 36 people. The data collection technique used a questionnaire. The data analysis technique used to answer the research hypothesis is multiple linear regression analysis. The results of this study indicate that: (1) Internal Control has an effect on performance-based budgeting at the Airport Office of Region VI-Padang, with a calculated t_value > t_table, namely 5.303 > 1.691 and a sig. value of 0.000 < (α) 0.05. (2) Organizational Commitment has a positive and significant effect on performance-based budgeting at the Airport Office of Region VI-Padang, with a calculated t_value > t_table, namely 3.032 > 1.691 and a sig. 0.005 < (α) 0.05. (3) Together, internal control and organizational commitment have a positive and significant effect on the use of performance-based budgeting at the Airport Office of Region VI-Padang, with F_count > F_table, namely 21.112 > 2.503 and a sig. 0.000 < (α) 0.05. The conclusion is that Internal Control and Organizational Commitment partially or simultaneously influence the use of performance-based budgeting at the Airport Office of Region VI-Padang. Theoretically, this research can help identify the success of peformance based budgeting, such as internal.control and organizational commitment. Meanwhile practically, this research can increase the efficiency and effectivenes of implementing performance based budgets in public sector organizations.